Obstacle Factors and Difficulty Factors for Students in Higher Education in Completing Final Assignments - Wahyudin Rahman; Loso Judijanto; Henny Sanulita (Journal of Education Reseach and Evaluation, 2024)
Procrastination often occurs in students in higher education. Facts in higher education in 2021-2022 from 27 students were found, and 22.22% of students had not taken part in a proposal seminar and had not completed a final assignment or thesis, 40.74% of students had attended a proposal seminar but had not completed a final assignment or thesis, and 37.03% of students had have attended a proposal seminar and have completed a final assignment or thesis. This problem is urgent to research because there is a gap between theory, expectations and reality on the ground. This research aims to analyze the factors that cause procrastination in students when completing their theses in higher education. The research method is mixed methods. The subjects were 50 students. Data collection techniques use questionnaires, interviews and direct observation of students. Analysis technique by collecting data, reducing and drawing conclusions. Data is depicted in diagrams, and the results of interviews and observations are interpreted. The results and research findings show that students working on their thesis have many difficulties caused by internal factors, namely self-control, self-efficacy, and lack of motivation. In the process of completing a final assignment or thesis, students are required to learn to motivate themselves, control themselves, and develop high self-efficacy so that students can focus more on completing their thesis.